A numerical study on the use of geofoam to increase the external stability of reinforced soil walls. Issue 6 (December 2008) - Hatami, K.; Witthoeft, A. F.
Abstract : The potential benefit of placing a panel of compressible (i.e. expanded polystyrene) geofoam behind the reinforced zone of mechanically stabilized earth (MSE) walls is investigated using a numerical modeling approach. A panel of geofoam is placed immediately behind the reinforced zone during the construction phase of an idealized plane-strain reinforced soil segmental wall model. The analysis procedure includes the modeling of soil compaction. The magnitudes and distributions of earth pressure behind the reinforced zone in the wall models with and without the geofoam panel are compared to quantify the reductions in lateral earth pressure, resultant lateral force and overturning moment expected due to the placement of the geofoam material. Predicted magnitudes of facing lateral deformation and reinforcement strains are also compared among cases studied in order to evaluate the effect of geofoam on wall serviceability. It is shown that placing geofoam behind the reinforced zone can reduce the maximum lateral earth pressure behind this zone by as much as 50% depending on the geofoam thickness and stiffness values. The magnitudes of total lateral earth force (i.e. the resultant force of the lateral earth pressure distribution) behind the reinforced mass and overturning moment about the wall toe are shown to decrease by 31% and 26%, respectively. These findings point to a significant potential for using geofoam to reduce the lateral earth pressure demand on MSE walls (i.e. as opposed to rigid retaining walls examined previously) and thereby increase their serviceability and their factors of safety against external instability.